MENINGKATKAN KEMAMPUAN MENGENAL HURUF VOKAL MELALUI MEDIA HURUF KERTAS AMPELAS BAGI ANAK DWON SYNDROME DI SLB SABILUNA PARIAMAN - Meta - Lestari (Universitas Negeri Padang, 2013)
Abstract These results indicate that, sandpaper letters media can increase children's ability to recognize vowels, it can be seen in the baseline phase in which children can only afford one of the five questions about the letter that researchers ask is seen in the third observation to observation of the fifth. After the intervention using sandpaper letters media shaped vowels, look first child can only answer one to five vowels of medium sandpaper letters and finally the child is able to answer all the vowels. Thus the hypothesis can be accepted that the media can enhance the ability of sandpaper letters recognize vowels in children with Down syndrome grade DI/CI in SLB Sabiluna Pariaman. The teacher and the researchers suggest further research in order to use sandpaper letters media to improve learning in Down syndrome children recognize letters.